GAME THEORY IN POLITICAL SCIENCE RESEARCH - Karas, Martin; Dančo, Ján; Čičková , Zuzana (PEOPLE: International Journal of Social Sciences, 2025)
This paper deals with the different ways that Game Theory is being used in Political Science research. The goal of the paper is twofold. First, it uses concrete examples of Political Science research to illustrate different ways that the Game Theory is employed to answer research questions and verify hypotheses in Political Science. Second, it analyzes these methods to show which avenues of use of Game Theory in Political Science are the most promising in terms of generating valuable insight into issues relevant to this scientific field.